Analysis of the Contextual Component of Forming Managerial Competence of the Future Manager of Educational Establishment - Darmanska, Iryna (Pedagogical Discourse, 2014)
The author clears up the question of forming managerial competence of the future managers of educational establishments. The content and the essence of the notion «managerial competence», and also its components have been revealed. The kinds of competences, which the manager should be able to use, as a professional, have been determined. Peculiarities of contextual component of forming managerial competence of the future managers of educational establishments have been revealed in more details. The contextual component of forming managerial competence of the future manager of educational establishment (pre-school, out-of-school, general educational) has been analyzed in the article. The analysis was done on the basis of Branch standard of preparation of managers of educational establishments on speciality «Management of Educational Establishment» (qualification «Manager of Enterprise, Institution, Organization in the Sphere of Education and Productive Studies») and curricula of higher educational establishments, which conduct preparation of the future specialists according to the mentioned standard. Taking into consideration education-qualification characteristics and educational-professional program of mastersʼ preparation on speciality «Management of Educational Establishment», the directions of the future specialistsʼ preparation have been determined. On the basis of generalizing, positive and negative sides of the process of preparation of managerial personnel for the sphere of education have been determined.